Penerapan Metode Multi-Objective Optimization on the Basis of Simple Ratio Analysis (MOOSRA) dalam Penentuan Lulusan Mahasiswa Terbaik - Karim, Abdul; Esabella, Shinta; Andriani, Titi; Hidayatullah, Muhammad (Forum Kerjasama Pendidikan Tinggi, 2022)
The problems that are often faced by the campus in the management of selecting the best students which are carried out once a year in a series of graduation events are the length of the process of calculating student data which is still done manually, criteria that have not been fulfilled optimally and are still based on value calculations alone, and processing is still manual. so that errors and data errors often occur which are quite fatal, subjective selection is still a common problem in the world of education so it is necessary to select outstanding students using a system. The system used is a decision support system that has the quality and logic of a method in a selective selection process with a high level of accuracy, while the method used is the MOOSRA method which is a decision support system method that is easy to understand and systematic stages that are easy to do. The results in this study were a student named Zainal as the owner of the highest score of 0.418397, accurate, efficient and effective results in the use of a decision support system made the selection process much more reliable